Archaeal Diversity and CO2 Fixers in Carbonate-/Siliciclastic-Rock Groundwater Ecosystems. (13th June 2017) - Lazar, Cassandre Sara; Stoll, Wenke; Lehmann, Robert; Herrmann, Martina; Schwab, Valérie F.; Akob, Denise M.; Nawaz, Ali; Wubet, Tesfaye; Buscot, François; Totsche, Kai-Uwe; Küsel, Kirsten
Abstract : Groundwater environments provide habitats for diverse microbial communities, and although Archaea usually represent a minor fraction of communities, they are involved in key biogeochemical cycles. We analysed the archaeal diversity within a mixed carbonate-rock/siliciclastic-rock aquifer system, vertically from surface soils to subsurface groundwater including aquifer and aquitard rocks. Archaeal diversity was also characterized along a monitoring well transect that spanned surface land uses from forest/woodland to grassland and cropland. Sequencing of 16S rRNA genes showed that only a few surface soil-inhabiting Archaea were present in the groundwater suggesting a restricted input from the surface. Dominant groups in the groundwater belonged to the marine group I (MG-I) Thaumarchaeota and the Woesearchaeota. Most of the groups detected in the aquitard and aquifer rock samples belonged to either cultured or predicted lithoautotrophs (e.g., Thaumarchaeota or Hadesarchaea). Furthermore, to target autotrophs, a series of 13 CO2 stable isotope-probing experiments were conducted using filter pieces obtained after filtration of 10, 000 L of groundwater to concentrate cells. These incubations identified the SAGMCG Thaumarchaeota and Bathyarchaeota as groundwater autotrophs. Overall, the results suggest that the majority of Archaea on rocks are fixing CO2, while archaeal autotrophy seems to be limited in the groundwater.